Pertanggungjawaban Publik Pemerintah dalam Perspektif Hukum Administrasi Negara - Ridwan HR (Fakultas Hukum Universitas Islam Indonesia, 2003)
One of principle in democratic legal state is legality, where every legal goverment action should be based on the authority mandated by regulation. Political and juridical account ability of authority holder is inherent with every form of goverment authority use, according with principle that no authority without accountability (geen behoegheid zonderverantwoordelijkheid)